Camera Raw with Photoshop for Dummies - Moss, Kevin L. (Wiley Publishing, 2011)
Offered by Canon, Nikon, Minolta, Sony, and other leading camera manufacturers, the Camera Raw format lets photographers create high-resolution "digital negatives"-uncompressed, unprocessed images that they can then manage and convert using Photoshop Cameras featuring Camera Raw capabilities are now priced as low as $300 This book explains what Camera Raw is, why serious amateur and professional photographers need it, and how to make the most of it using Photoshop's powerful Camera Raw plug-in Topics covered include evaluating and working with Camera Raw images, harnessing Photoshop Camera Raw tools, using metadata, understanding color, and correcting images